(untitled) (Research, Society and Development, 2020)
Introdution: The new coronavirus is called SARS-CoV-2, however it causes Severe Acute Respiratory Syndrome (SARS). This virus is easily transmitted from person to person through contact with contaminated surfaces, as well as through aerosols, this according to the World Health Organization (WHO), but it is non-definitive evidence, and which is likely to be more propitious in places with poor ventilation and crowding. It results from symptoms such as: fever, cough, fatigue, dyspnoea, loss of smell and taste; and less frequent headache, throat and diarrhea. Objective: to analyze the association between worsening comorbidities, age and SARS-CoV-2 infection. Methodology: this research is of qualitative / quantitative property, with an exploratory and descriptive attribute, fostered through secondary data extracted from scientific articles from indexing sources, in the year 2016, 2018 and 2020, with language: English, Spanish and Portuguese. Results: it aims to understand the disease through statistical data through the amount of death by COVID-19, age group, the most prominent comorbidity, the most notified sex, and comparisons between deaths in Brazil due to neoplasms (breast, prostate) and deaths from cardiomyopathies, diabetes, obesity, COVID-19 and unspecified SRAG. Final considerations: Therefore, the best ways to prevent this pathology is social isolation, and to avoid possible agglomerations, since the gradual growth of deaths by COVID-19 has a great relationship both with the present comorbidities and with advanced age, therefore, people at risk should redouble their care.